(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Lovyanova I. V., Bobyliev D. Ye. The system of professionally oriented skills of students in the process of functional analysis training. On the basis of the comparison, contrast, generalization of scientific information, analysis of structural and logical schemes and content of propaedeutic course of functional analysis professional oriented skills, which are nessecary to form within this course were selected. The basic requirements to the organization of the functional analysis training of future Mathematics teachers on the basis of introduction of methodical system of professionally oriented training which promotes students’ professionally oriented skills were examined.